Correction: Discovery and characterization of functional modules and pathogenic genes associated with the risk of coronary artery disease. Issue 37 (25th April 2015) - Nie, Wenna; Lv, Yana; Yan, Leyu; Guan, Tianbing; Li, Qiang; Guo, Xiaojuan; Liu, Wenhu; Feng, Mengpei; Xu, Guang; Chen, Xi; Lv, Haitao
<x xml:space="preserve">Abstract</x> Correction for 'Discovery and characterization of functional modules and pathogenic genes associated with the risk of coronary artery disease' by Wenna Nie et al., RSC Adv., 2015, 5, 26443–26451.